Upaya The Nature Conservancy Dalam Konservasi Terumbu Karang Dan Lingkungan Pesisir Di Kawasan Perairan Nusa Penida, Bali - Savitri, Santhi Pradayini; Wiranata, S.IP, M.A, I Made Anom; Kawitri Resen, S.IP. M.A, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRAK Environmental issues have become an International Primary agenda. The high threat from global warming and the destructive actions increase the risk of damage to the marine environment and coral reefs. Regarding that issue, Non-Governmental Organization (NGO) play important role in developing sustainability of the marine environment. The Nature Conservancy (TNC) is one of International NGO that paying attention on environmental issues in Indonesia by creating Coral Triangle Center (CTC) program in 2000. TNC has made various efforts in the conservation of coral reefs and coastal environment in the waters of Nusa Penida, Bali. That effort consist of public education, capacity building, and increasing public environmental awareness, research marine resources, and initiating a policy through the conservation area. Furthermore, The Nature Conservancy has helped local communities to initiate a policy that supports the conservation of coral reefs and coastal environment in the waters of Nusa Penida Bali. Key words: Conservation, The Nature Conservancy, Coral Reef